Utilization of Digital Marketing Platform to Increase Brand Awareness of Natural Bodycare Making Course at Necerel - Hutabarat, Debora; Sandy, Rama; Setiawan, Risqi Firdaus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Digital marketing encompasses promotional activities and market research conducted through online digital media, utilizing various platforms such as social networks. Brand awareness plays a crucial role in marketing by introducing a brand or product to the public. This study aims to enhance Necerel's brand awareness and market reach, encouraging consumers to consider and ultimately purchase its services. The methods employed included discussions and interviews with mentors and supervisors, followed by hands-on practice as a digital marketer at Necerel. This involved content design, strategy implementation, and subsequent evaluation and improvement. The internship yielded the following results: 1. An increase in the target market, followers, and views on Necerel's social media platforms due to effective digital marketing strategies. 2. Enhanced trust among potential customers towards Necerel's e-commerce platform for promoting products and services. 3. Improved visibility and credibility of Necerel through the development of a website, landing page, and Google Maps presence, providing potential customers with comprehensive information.